Epistemic Violence Toward Immigrant Women in Iceland: Silencing, Smothering, and Linguistic Deficit - Kjaran, Jón Ingvar; Halldórsdóttir, Brynja E. (Nordic Journal of Migration Research, 2022)
This paper is an examination of how stories shared as a result of the #metoo movement in Iceland exemplify aspects of how culture and institutions in Iceland are complicit in the silencing of immigrant women who experience violence, both in intimate partner and employment situations. Through a critical analysis of 10 of the narratives shared by immigrant women in Iceland, the authors explore how testimonial smothering and silencing are both producing and reproducing epistemic violence in the women’s lives. We argue that the focus on linguistic purity of the Icelandic language maintains these exclusionary practices. Recognition of hegemonic practices is important in the continued development of a more equitable society and a first step in the inclusion of diverse voices in the continued development of the diversifying Icelandic knowledge society.